Comparison of Outcomes of Primary Repair Versus Ileostomy in Typhoid Ileal Perforation in Different Age Groups - Jamshed Khan, Abdul Latif, Muhammad Hanif, Muhammad Umar, Ahmad Zeb, Ajmal Khan Bazai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Procedure of ileostomy in patients of Typhoid fever perforation with friable gut defunctions the diseased gut, repair the infected fecal matter, protects the intestinal repair done in septic tissues and reduces the anastomotic dehiscence. Method: This was a Randomized controlled study. Started in November 2015 to May 2016 at BMC Hospital balochistan. Main objectives were to compare the infectionof postoperative wound between ileostomy and primary closure in patients undergoing surgery for Typhoid fever ileal perforation. Study done by One fifty patients who underwent Typhoid fever perforation surgery. The surgical management was done as primary repair (group-A) and ileostomy (group-B). Postoperative complications were evaluated till 5 days of hospital stay. Comparison between two groups was done using chi square. Stratification was done and p-value ≤0.05 was considered as significant. Results: In group-A 47 male and 28 females and in group-B 52 male and 23 female patients were included. In group-A, 40 Percent observed wound discharge while in group-B it was 24 Percent. In group-A, acceptable comesis were observed for 80 Percent patients and in group-B, it was 93.3 Percent. Results showed significant association of wound discharge and acceptable cosmesis with the two study groups. Conclusion: Better outcome in ileostomy group than primary repair group was significant observed in the study. Keywords: Typhoid fever , Salmonella Typhi Acceptable cosmesis, Wound Discharge, Intra Abdominal Collection, Ileostomy, Typhoid fever Ileal Perforation